Evaluation of Grain Yield Potential and Environmental Stability of the Barley Genotypes Using an Augmented Randomized Complete Block Design - Pokharel, Bhanu Bhakta; Timalsina, Himal Prasad; Ghimire, Krishna Hari; Subedi, Sushil Raj; Bhattarai, Rajendra; Chaulagain, Bhimsen; Adhikari, Parbati; Upadhyaya, Jagat Prasad; Thapa Magar, Devi Kumari (Agronomy Journal of Nepal, 2025)
In initial breeding field trials, insufficient seed quantity and limited land area frequently hinder complete replication, complicating the precise evaluation of genotypic potential due to environmental variability. This study aims to assess the grain yield performance of 336 unreplicated barley genotypes in conjunction with six replicated check varieties, employing an Augmented Randomized Complete Block Design. The experiment was carried out in 10 blocks for three consecutive years. To figure out how many environmental errors there were, six check varieties were repeated in each block. In contrast, 336 barley genotypes were tested without replication. The analysis result showed that the environment was different, with block mean yields for checks ranging from 2422 kg ha-1 (Block 9) to 3407 kg ha-1 (Block 6). Because of this change, genotypes in stress environments had to have their yields changed by as much as +585 kg ha-1. Genotype AM-292 was the best line, with the highest adjusted yield (8392 kg ha-1), showing that it did very well even though it was grown in the block with the least fertile soil. Genotype AM-159 (7902 kg ha-1) and Genotype AM-185 (7206 kg ha-1) were also chosen as the best performing genotypes. The check variety “V. Morales” was very stable, while the check variety “Alanda” showed a lot of phenotypic variation (2374–5755 kg ha-1), which made it less useful as a stability reference. The improved design worked well to reduce environmental error. The top 10% of genotypes have been chosen (higher than 5000 kg ha-1 yield potential) based on their adjusted yield performance.